A retreatment of an endodontic tooth 25 with underfilled - Cahyani, Febriastuti; Adita, Farah Rahmi; Rachmawati, Atika Nisaa; Haq, Addina Ainul; Fadila, Okta Mulia Nur; Cinantya, Aulia Dian; Pribadi, Nirawati (Conservative Dentistry Journal, 2023)
Background: Cases of endodontic failure requiring retreatment are endodontic failure cases in which microorganisms in root canal are able to survive, causing inflammation and pain. Purpose: This research aims to carry out retreatment of teeth after endodontic treatment to maintain and improve its function. Case: Male patient (67 years) has suffered from pain when chewing and discolored upper left second premolar tooth since one year ago in 2022. Ten years ago in 2013, he got dental treatment for the tooth. The patient also has a history of controlled hypertension. Case management: Several stages were conducted in sequence, namely gutta percha removal from previous endodontic treatment, root canal re-preparation, irrigation sequence, dressing, and obturation with single cone technique. Conclusion: In this case, an indirect restoration in the form of a crown should have been conducted to obtain a good contact point. As a result, food retention occurred in the interdental area, and then microorganisms entered through the periodontal tissue, causing periodontal inflammation. The inflammation then spread apically until it entered one-third of the apical in root canal, resulting in periapical inflammation. Exposed dentinal tubules in the missing portion of cementum then cause bacterial invasion of the tubules and increase the possibility of damage to the pulp. Periodontal disease can progress apically and involve the apical foramen. In this case, an indirect crown restoration was used since the quality of the final restoration has an impact on the survival and success rate of the endodontically treated tooth. In conclusion, a well-sealed crown restoration will prevent the entry of microorganisms